Manajemen Pendidikan Karakter dalam Mewujudkan Generasi Berakhlakul Karimah di SMP Negeri 4 Purworejo - Dukhri Muhamad (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This research is based on the importance of akhlakul karimah. In this regard, this study aims to determine the management of character education in creating a generation with good morals at SMP Negeri 4 Purworejo. This research is a qualitative research. Data collection used interviews, observation, and documentation, and the validity of the data used triangulation, and data analysis techniques included data reduction, data presentation, and drawing conclusions. The results of this study indicate that: (1) The inculcation of values ​​and morality in creating a generation of good morals at SMP Negeri 4 Purworejo is carried out by the principal, teachers and staff and all school members. The teacher integrates character through learning lesson plans and through school extra-curricular activities, providing motivation. (2) Modeling of values ​​and morality in creating a generation with good morals is carried out by the principals of all teachers and employees as well as parents. They realize that their behavior is a model for their students. Therefore all school members are always careful in behaving and speaking in front of students at school. (3) SMP Negeri 4 Purworejo facilitates values ​​and morality in creating a generation of good morals. Schools provide opportunities for students to solve problems related to school activities. The school principal, employee teachers always listen seriously to students' complaints and suggestions. The teacher involves students directly so that it influences the character of students. (4) The development of values ​​and moral literacy in creating a generation of good morals is carried out by SMP N 4 Purworejo to provide critical, creative thinking skills and communicate clearly. (5) Developing a values ​​education program to create a generation of good morals that is carried out by SMP N 4 Purworejo, namely by including it in extra-curricular learning.